Pengaruh Integrasi Laboratorium Virtual dalam Model Pembelajaran Problem Solving Terhadap Kemampuan Berpikir Kritis Peserta Didik pada Materi Elektrolit dan Non elektrolit - Dwi Afni Musyaillah; Sukro Muhab; Yusmaniar (LPPM Universitas Negeri Jakarta, 2020)
The purpose of this study was to determine the positive effect of virtual laboratory integration in Problem Solving learning models on students' critical thinking skills in the electrolyte and non-electrolyte solution materials. This research was conducted in December 2018 - May 2019. The quantitative research method used was a quasi-experiment with Posttest Only Control Group Design. This research consisted of experimental class and control class, with 36 students in each class. The experimental class applies virtual laboratory integration learning in the Problem Solving learning model, while the control class applies 5M learning. The results showed that the average posttest value of the experimental class was 72.8 and the control class was 63.7. The results of the testing of the hypothesis were obtained by the value of t count (4.942)> t table (1,667) with a value with a significant level of 0.05, indicating that the positive influence of virtual laboratory integration in the Problem Solving learning model on students' critical thinking abilities in electrolyte solution material and nonelectrolytes. KeywordsVirtual Laboratory, Problem Solving, Critical Thinking Ability, Electrolyte and nonelectrolyte